Active learning-based systematic reviewing using switching classification models: the case of the onset, maintenance, and relapse of depressive disorders - Teijema, Jelle Jasper; Hofstee, Laura; Brouwer, Marlies; de Bruin, Jonathan; Ferdinands, Gerbrich; de Boer, Jan; Vizan, Pablo; van den Brand, Sofie; Bockting, Claudi; van de Schoot, Rens; Bagheri, Ayoub (Frontiers in Research Metrics and Analytics, 2023)
Introduction This study examines the performance of active learning-aided systematic reviews using a deep learning-based model compared to traditional machine learning approaches, and explores the potential benefits of model-switching strategies. Methods Comprising four parts, the study: 1) analyzes the performance and stability of active learning-aided systematic review; 2) implements a convolutional neural network classifier; 3) compares classifier and feature extractor performance; and 4) investigates the impact of model-switching strategies on review performance. Results Lighter models perform well in early simulation stages, while other models show increased performance in later stages. Model-switching strategies generally improve performance compared to using the default classification model alone. Discussion The study's findings support the use of model-switching strategies in active learning-based systematic review workflows. It is advised to begin the review with a light model, such as Naïve Bayes or logistic regression, and switch to a heavier classification model based on a heuristic rule when needed.